Assembly of an Achiral Chromophore into Light‐Responsive Helical Nanostructures in the Absence of Chiral Components. Issue 12 (2nd February 2016) - Han, Mina; Cho, Sung June; Norikane, Yasuo; Shimizu, Masaki; Seki, Takahiro
Abstract: The chirality found in living organisms is one of unsolved mysteries on Earth. It is crucial to understand the manner in which small achiral molecules evolve into helical superstructures in the absence of chiral components because this process can provide important insights regarding the origin of chirality in nature. 1) the uncommon helical assembly of an achiral trigonal chromophore into helical nanostructures with aggregation‐induced emission enhancement (AIEE) characteristics and 2) the tunability of the helical pitch and fluorescence intensity in response to light is reported. The Rietveld refinement of X‐ray diffraction (XRD) patterns and the growth process suggest that a striking transformation from an achiral to an asymmetric molecule can occur as a result of specific interactions with certain solvents, presumably leading to the unique helical assembly. More importantly, exposure to UV or visible light promoted not only the formation of irregular helical structures with a wide range of pitch lengths but also an increase in fluorescence intensity. Abstract : The uncommon helical assembly of an achiral chromophore into fluorescent helical nanostructures in the absence of chiral components and the tunability of the helical pitch and fluorescence intensity in response to light are reported. A marked transformation from an achiral to an asymmetric molecule can occur as a result of specific interactions with certain solvents, presumably leading to the unique helical assembly.